2023
DOI: 10.1186/s43054-023-00201-x
|View full text |Cite
|
Sign up to set email alerts
|

Population knowledge and commitment regarding a child’s car safety seat after implementation of the new traffic regulations in Saudi Arabia: a cross-sectional study

A. Alsaeigh,
ES. Heji,
W. Alamer
et al.

Abstract: Objective This study aimed to evaluate the understanding and adherence to child car safety seat (CSS) guidelines among the general population in the Makkah region of Saudi Arabia following the implementation of new traffic regulations. Method A four-section questionnaire addressing knowledge and attitudes regarding CSSs was distributed among the general population of Makkah city in light of new traffic regulations. Data were collected from 487 resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This result is probably due to the fact that HCW with underage children also learned from their own experience and likely searched for RT prevention information compared to those without kids or with older children, since in the past there were very few or no such clear recommendations and regulations for child traffic safety. A recent study from Saudi Arabia demonstrated that parents with two underage children and those with higher education had better knowledge of child car safety seat regulations ( 32 ). The same study assessed the independent predictors of good knowledge and found that only age and education were among the demographic factors significantly associated with better knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This result is probably due to the fact that HCW with underage children also learned from their own experience and likely searched for RT prevention information compared to those without kids or with older children, since in the past there were very few or no such clear recommendations and regulations for child traffic safety. A recent study from Saudi Arabia demonstrated that parents with two underage children and those with higher education had better knowledge of child car safety seat regulations ( 32 ). The same study assessed the independent predictors of good knowledge and found that only age and education were among the demographic factors significantly associated with better knowledge.…”
Section: Discussionmentioning
confidence: 99%